STRATEGIES FOR DEVELOPING STUDENT LEARNING THROUGH PEDAGOGICAL IMPROVISATION IN THE HIGHER EDUCATION PROCESS - Ergasheva Muhayyokhon Ganijonovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  This  article  analyzes  the  role  and  importance  of  pedagogical improvisation strategies in the development of students' learning activities in the higher education system . The issues of organizing education on a heuristic and creative basis, abandoning traditional approaches, and in particular, adapting the educational process based on the needs of the student are highlighted. Also, psychological and pedagogical mechanisms for transforming external motivation into internal (intrinsic) motivation in students  and  forming  skills  for  applying  knowledge  in  non-standard  situations  are studied.